PENONTON SEBAGAI AKTOR SOSIAL: HIPERREALITAS DAN PEMAKNAAN TERHADAP SERIAL DRAMA KOREA - Rani Titis Sukowati; Ika Agustina; Ayu Riyanti (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
Korean television dramas have become one of the most popular forms of popular culture enjoyed by audiences. A number of previous studies have examined mass media exposure to Korean television dramas, hyperreality in films and dramas, and the effects of such media texts on audiences, often positioning viewers as passive subjects who experience relatively uniform impacts. This article argues that audiences are not passive social actors but active ones, therefore, the hyperreality offered by Korean television dramas does not produce identical effects for every viewer. This study employs a qualitative approach using in-depth interviews with viewers of Korean television dramas in the romance, drama, and comedy genres, supported by a review of relevant literature. The findings indicate that Korean television dramas consistently present narratives of romanticism, however, the processes of interpretation and reception vary among viewers. Some audiences develop new values and perspectives, particularly regarding romance, partnerships, friendships, and family, while others position these dramas merely as entertainment without influencing their everyday lives. These findings affirm that hyperreality in popular culture does not operate in a deterministic manner but is mediated by viewers’ experiences, preferences, and social backgrounds.